Pestisida Dan Upaya Detoksifikasi Residu Tercemar Secara Biologik - Yunisyaaf Y A (Jurnal Kimia dan Kemasan, 1985)
Nowdays the use and production of pesticide in Indonesia being increase. In agricultural fields, pesticide was essential for increasing the yield of plant. Beside that, pesticide could make ecosystem balance. Many of pesticide, for example halogenated compound are extremely persistent in nature. But recent experiment showed that persistent residue of pesticide could slowly eliminated by two special mechanism, firstly by bioaccumulation process and the other was by biodegradation process. These biomechanism were the most unique process, because it occur through nature mechanism that present in organism itself.